"You're Supposed to Help Me": The Perils of Mass Counseling Norms for Working-Class Black Students. (October 2021) - Gast, Melanie Jones
How do educators reconcile the growing college-for-all norm—the notion that all students should pursue college—with the diverse needs of students in urban settings? What is the impact on Black students across social-class background? Using interviews and fieldwork with teachers, counselors, and diverse Black students in a large Californian high school, I examine college-counseling norms under a social capital framework. With high caseloads, I find that educators support mass outreach and vague encouragements for 4-year colleges. Ultimately, my findings problematize one-size-fits-all counseling norms and highlight the need for more targeted counseling for urban and working-class Black students.